An Andean Musical Structure That Defies Borders - Camara de Landa, Enrique (European Journal of Musicology, 2022)
In many existing repertoires of traditional music in the South American Andean area a type of melodic structure that seems to refer to a common antecedent can be detected, even though its adaptation to the various genres is manifested through musical variants. The comparative analysis of these expressions (some belonging to the heptatonic modal and tonal systems of European origin and other that are typical of the anhemitonic pentatonic Andean system) allows a possible influence of the latter on the former to be hypothesized.This proposal aims to advance in this direction and will try to highlight one of the characteristics that give cohesion to musical expressions from a cultural area affected by processes of transculturation and identity affirmation. To achieve new knowledge about this phenomenon one has to analyze both the musical structures and the implications of its use in repertoires emerging at different times and in different circumstances, linked to the search and affirmation of an Andean cultural identity through organized sound.